Continuous auricular acupuncture and daytime intermittent electroacupuncture as a complementary therapeutic improve glycemic variability and stability under Continuous Glycemic Monitoring System in hospitalized diabetic patients - Jin, Jianlan; Wen, Song; Liu, Haiyan; Chen, Lijiao; Ren, Yishu; Gong, Min; Yuan, Xinlu; Li, Jiyu; Zhou, Ligang (Frontiers in Endocrinology, 2026)
ObjectiveThis study aimed to evaluate the effects of continuous (24h) Auricular acupuncture (AAC) alone and combined with intermittent (20–30 mins daytime, three times per week) Electroacupuncture (EAC) on blood glucose variability (GV) and stability via (Con) CGMS. This approach goes beyond mean glucose levels and could serve as a key determinant of metabolic instability and complication risk in diabetes. The study focused on hospitalized patients with Diabetes Mellitus (DM) and explored their distinct roles across different diurnal segments.MethodsThis retrospective study, conducted at the Department of Endocrinology from 2023 to 2025, analyzed Continuous Glucose Monitoring System (CGMS) data from categorized patient groups (CGMS control, AAC, and AAC+EAC, n=984). Statistical analyses focused on overall mean blood glucose (MBG) and segment-specific (24h, 0-4h, 4-8h, 8-20h, 20-24h) ambulatory glucose profile (AGP) percentiles.ResultsNo significant difference in 24-hour MBG was observed among groups (P = 0.9297). Both AAC and AAC+EAC significantly reduced higher glucose percentiles (P75, P90, P95) across 24 hours and during daytime (8-20h) compared to controls. AAC alone was shown to have lower MBG in mid-to-high glucose ranges (P25-P95) during non-EAC periods (0-4h, 4-8h, 20-24h). Both AAC and AAC+EAC groups consistently exhibited significantly higher MBG at lower percentiles (P5, P10) than controls during all segments (0-4h, 4-8h, 20-24h). Notably, during daytime (8-20h), AAC+EAC showed significantly higher P5, P10, and P25 values compared to controls and AAC alone.ConclusionContinuous AAC and daytime intermittent EAC effectively reduce glycemic variability in hospitalized patients. AAC provides sustained, broad-spectrum control over glycemic fluctuations in higher percentiles. Daytime EAC uniquely helps prevent lower glucose excursions during its use, indicating a protective role against daytime hypoglycemia. These findings support personalized, complementary interventions for optimized diabetes management.